Estimation of Unknown Object Measures in a Chemical Weighing Design with Correlated Errors - Graczyk, Małgorzata; Ceranka, Bronisław (Acta Universitatis Lodziensis. Folia Oeconomica, 2024)
In this paper, some problems that concern the determining of unknown measurements of objects in the model of a chemical balance weighing design are presented. These designs are tested under the assumption that measurement errors are correlated and have the same variances. The relations between the parameters of a weighing design are considered from the point of view of the D-optimality criterion. We give some conditions determining the dependencies between the parameters of such designs and construction examples.